(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The process of economic and social development of a country requires the advancement of the reality of all economic sectors, particularly the industrial sector, through sober scientific remedies based on ensuring the optimal use of material and human energies and allowing the best ways to exploit them and avoid waste, loss, and suffocation. Iraq’s industrial sector is of exceptional importance because together with the agricultural sector.It is the heaviest sector of the national economy. It represents the most effective and dynamic sector in economic development through its direct impact on the development process and other sectors with which it is increasingly contributing to the development process. Within the industrial sector, the manufacturing sector emerges as an important sector that directly contributes to constructing the country’s strong industrial base, which can be relied upon in thefuture. The manufacturing sector is broad and complex, encompassing those industries that require the introduction or transformation of various mechanical, chemical, natural, and compositional means to change their nature, image, and shape and make them ready for new uses. One of the most widespread manufacturing branches is the textile industry because of the provision of clothing and clothing to the population and their significant contribution to reducing reliance on imports and the operation of national labor as laborintensive industries. It also has a role in increasing national income because it relies primarily on domestic production requirements. The development and growth of textile industries, in general, requires the protection of the national product to achieve greater capacity in local markets. The men’s clothing factory in Najaf is one of the formations of the General Company for Textile and Leather Industries under the Iraqi Ministry of Industry and Minerals, characterized by its diversity of products and importance and the large production and size of capital invested in its assets. On this basis, the subject of the study was chosen under the title. The research aims to identify the factory’s performance efficiency level for the duration (2010 -2020) by using the performance efficiency evaluation process criteria.